2010
DOI: 10.1159/000321967
|View full text |Cite
|
Sign up to set email alerts
|

The Meaning of Interaction

Abstract: Although recent studies have attempted to dispel the confusion that exists in regard to the definition, analysis and interpretation of interaction in genetics, there still remain aspects that are poorly understood by non-statisticians. After a brief discussion of the definition of gene-gene interaction, the main part of this study addresses the fundamental meaning of statistical interaction and its relationship to measurement scale, disproportionate sample sizes in the cells of a two-way table and gametic phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
120
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 127 publications
(120 citation statements)
references
References 46 publications
0
120
0
Order By: Relevance
“…Finally, we point out that an interaction detected via statistical models is different from the biological interaction (Phillips 1998;Cordell 2002;Wang et al 2010). The lack of direct correspondence between statistical and biological interactions makes it difficult to make strong inferences concerning biological mechanisms based on interaction terms from a statistical model (Ueki and Cordell 2012).…”
Section: Phenotypic Variability and Implications In Complex Traits Anmentioning
confidence: 87%
“…Finally, we point out that an interaction detected via statistical models is different from the biological interaction (Phillips 1998;Cordell 2002;Wang et al 2010). The lack of direct correspondence between statistical and biological interactions makes it difficult to make strong inferences concerning biological mechanisms based on interaction terms from a statistical model (Ueki and Cordell 2012).…”
Section: Phenotypic Variability and Implications In Complex Traits Anmentioning
confidence: 87%
“…Modern statistical modeling techniques are required for discovering statistical interactions of multiple genetic variants in the context of potential complicating factors, such as multiple genetic markers, linkage disequilibrium (LD), and environmental influences. In addition, because of the smallness of (marginal) main-effects (Wang, Elston & Zhu, 2010), predictive variables are often associated with only a small increased risk of disease, indicating that each has only a small individual predictive value. In statistical terms, we would hypothesize that sets of weakly predictive variables can be jointly predictive.…”
Section: Introductionmentioning
confidence: 99%
“…Third, the calculated interaction model is hard to explain. A previous study has reported that this might result from biological interactions between the variants or their products [9].…”
mentioning
confidence: 97%